2010
DOI: 10.1111/j.1553-2712.2010.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly Tracks in Emergency Medicine

Abstract: Over the past decade, some residency programs in emergency medicine (EM) have implemented scholarly tracks into their curricula. The goal of the scholarly track is to identify a niche in which each trainee focuses his or her scholarly work during residency. The object of this paper is to discuss the current use, structure, and success of resident scholarly tracks. A working group of residency program leaders who had implemented scholarly tracks into their residency programs collated their approaches, implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 4 publications
0
48
0
Order By: Relevance
“…Initially a feature of only a select few programs when they were created around 2002, 1 scholarly tracks are now a core feature of numerous residency programs across the nation. As faculty positions in academic medicine continue to require greater degrees of specialized training, 2 residencies have recognized the need to prepare residents for this new reality and success in academia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially a feature of only a select few programs when they were created around 2002, 1 scholarly tracks are now a core feature of numerous residency programs across the nation. As faculty positions in academic medicine continue to require greater degrees of specialized training, 2 residencies have recognized the need to prepare residents for this new reality and success in academia.…”
mentioning
confidence: 99%
“…The form of this focused study can vary-residents may undertake research projects and grant applications, independent study, teaching opportunities, or dedicated rotations devoted to their scholarly track depending on the student's interests and the capabilities of the residency. 1 Preliminarily, scholarly tracks seem to be successful -greater academic productivity during residency has been correlated with a greater number of residents choosing academic careers. 5 Some success has also been shown with measuring outcomes of scholarly tracks in other specialties-an obstetrics track at a family medicine residency program found that its residents performed similarly to obstetrics and gynecology residents on examination scores and number of procedures performed, 6 and a new global health track at a different program achieved high scores on resident evaluations.…”
mentioning
confidence: 99%
“…Each 48-month program may use their additional training time to meet their own unique program-specific aims 7,8,11. The supplemental milestones described in this study were developed with the intention that they might serve as a potential tool to assess and track already-existing curricula.…”
Section: Discussionmentioning
confidence: 99%
“…The EM Milestones are used by all ACGME-accredited EM residency programs, regardless of program length 1. However, EM residency programs with a 48-month training format are expected to provide the RRC-EM with “justification describing the additional educational goals and outcomes to be achieved by residents in the incremental 12 months of education.”1 Different programs use this additional training time in different ways, including extra elective time, built-in mini-fellowships, scholarly tracks, and other means of academic and professional development 7. The EM Milestones were not designed to reflect the “additional educational goals and outcomes” of 48-month residency programs, but rather were intended to evaluate resident progress during training irrespective of program length 1…”
Section: Introductionmentioning
confidence: 99%
“…1 It was an excellent review of the concept, providing examples of implemented tracks at a small sample of training programs. To my disappointment (although no fault of the authors), there was no mention of the narrative.…”
mentioning
confidence: 99%